2021
DOI: 10.1186/s12903-021-01536-w
|View full text |Cite
|
Sign up to set email alerts
|

An experimental intraradicular biofilm model in the pig for evaluating irrigation techniques

Abstract: Background We established an in vivo intraradicular biofilm model of apical periodontitis in pigs in which we compared the efficacy of different irrigant activation techniques for biofilm removal. Methods Twenty roots from the deciduous mandibular second premolar of 5 male pigs were used. After pulpectomy, canals were left open for 2 weeks and then sealed for 4 weeks to enable the development of an intracanal biofilm. The intraradicular biofilms wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 68 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…16 Others include interruption of molecular system of biofilm formation and irrigation techniques including passive ultrasonic, subsonic, or laseractivated irrigation for removal of root canal biofilms. 17,18 Among these techniques, the use of phagebased strategies was least emphasized, whereas they are economical and potentially modifiable. It is thus essential to discuss phages and bacterial biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…16 Others include interruption of molecular system of biofilm formation and irrigation techniques including passive ultrasonic, subsonic, or laseractivated irrigation for removal of root canal biofilms. 17,18 Among these techniques, the use of phagebased strategies was least emphasized, whereas they are economical and potentially modifiable. It is thus essential to discuss phages and bacterial biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, non-contact bio lm removal techniques continue to need a more reliable retreatment protocol. We have previously reported an in vivo intraradicular bio lm model in the pig [17], which can closely replicate human bio lms in terms of morphology and microbiota, to evaluate the effectiveness of bio lm removal protocols and found that LAI is an effective intervention in this regard 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was performed using ANOVA followed by a Tukey Kramer post-hoc test with an α value of 0.05 (BellCurve for Excel; Social Survey Research Information Co., Ltd. Tokyo, Japan) to detect signi cant differences in the bacterial populations. SEM sample preparation was conducted according to previously described methods [17,18]. Brie y, after resecting the tooth crown, the mesial and distal roots were separated with a diamond disc.…”
Section: Methodsmentioning
confidence: 99%
“…To induce intracanal bio lm is following the previously reported procedure [17]. Brie y, the occlusal surface was attened using a straight bur and electric engine (Ti-Max X95; NSK, Tochigi, Japan) to prevent tooth fracture and for the ease of working length determination.…”
Section: Page 4/13mentioning
confidence: 99%
“…Statistical analysis was performed using ANOVA followed by a Tukey Kramer post-hoc test with an α value of 0.05 (BellCurve for Excel; Social Survey Research Information Co., Ltd. Tokyo, Japan) to detect signi cant differences in the bacterial populations. SEM sample preparation was conducted according to previously described methods [17,18]. Brie y, after resecting the tooth crown, the mesial and distal roots were separated with a diamond disc.…”
Section: Page 4/13mentioning
confidence: 99%